Pemanfaatan Google Form Sebagai Media Pembelajaran Bagi Guru SD Di Masa Pandemi Covid-19 - Rumyati Rumyati (Jurnal Pengabdian Masyarakat PGSD, 2021)
Google Form was one of Google's services primarily used in educational settings. One of its functions is to conduct surveys. Google Form can make learning neater. Many schools studied and used Google Forms as an alternative learning media during the Covid-19 pandemic. Unfortunately, it was assumed that Google Form was only operated in the survey or research activity even though it had much potential to be explored. Therefore, this community service activity focuses on assisting teachers in using the Google Form. The method in this activity is to provide an introduction and socialization about using Google Forms for teachers. This activity's target was teachers at State Elementary School of Panancangan 2. Through this activity, it is hoped that teachers at State Elementary School of Panancangan 2 can find out the benefits and use of Google forms. This community service aims to get an idea of the extent to which teachers in schools use Google Forms and help them develop the use of Google Forms in learning. The results of this activity are that teachers could use Google Forms, and students have the facilities and infrastructure to carry out online education. After a good understanding of the potential of Google Form, the teacher was expected to keep progressing delivery to other platforms to help them conduct online learning.